Identifikasi Cendawan Patogen Beberapa Varietas Benih Kacang Tanah (Arachis hypogaea L.) Pada Beberapa Tempat Penyimpanan yang Berbeda di Kecamatan Insana Barat - Yunita Alberta Kono (Fakultas Pertanian, Universitas Timor, 2021)
This study aims to identify the patogenic fungi of peanut seeds in several storage areas in the West Insana District and obtain an appropriate storage place for peanut seeds. The study was conducted at the Laboratory of the Faculty of Agriculture, University of Timor, East Nusa Tenggara, in February-March 2020. The design used in this study was to use a completely randomized design (RAL) with 2 factorial. The first factor is the storage area (P) consists of 3 levels, namely: plastic sacks (P1), socal (P2), cans (P3). The second factor is the type of variety (V) consisting of 3 arsas, namely local red peanuts (V1), local white peanuts (V2), and striated peanuts (V3). Each treatment combination was repeated three times so that there were 27 experimental units. Based on the results of the study, there were 4 contaminant fungi contaminating peanut seeds including fusarium sp, Aspergilus sp, Melanospora sp, and Rhizopus sp. Canned storage models and striated peanut varieties provide the lowest patogenic insects when storing. Testing the viability of peanut seeds on the maximum maximum growth potential parameters there are peanut seeds from the storage model with a percentage of 91.56%, germination capacity in storage with a percentage of 90.22%, and a vigor index 85.78% higher from the storage model in the sack.